Pengaruh Penggunaan Media Sosial Terhadap Perkembangan Anak (Survei di Pulo Gebang Rt. 003/004 Jakarta Timur) - Ishak Syairozi; Kunaenih; Rizky Pajar Perdana; Romi Syahrial; Nur Sabha Alfiyani; Millah Fadilah (STIT Muslim Asia Afrika, 2022)
This research is motivated by the reality of the conditions that exist in the RT.003/004 Pulo Gebang East Jakarta, where children aged 12-18 years are often seen playing without time limits and not far from Handphone. The purpose of this study was to determine whether there is an influence of use social media on children's development and to find out how big the influence of that. This research is a quantitative research using correlational analytic descriptive method. This research took place at Jalan Pulo Gebang RT.003/004 Pulo Gebang Village, Cakung District, East Jakarta. This research lasted for 3 months, starting from October – December 2021, in this study involving the Head of the Neighborhood Association (RT), dasawisma cadres, and young people around the area where the research was carried out. To obtain data, it is done by means of observation and questionnaires. The data analysis is descriptive analytic correlational, which describes systematically and accurately about the population or about a particular field, then analyzes and presents the data systematically. Based on the results of the study, obtained data on the Influence of using social media on child development in Pulo Gebang RT.003/004 East Jakarta, namely there is an influence of using social media on child development in Pulo Gebang RT.003/004 East Jakarta and based on the results of the analysis of the magnitude of the effect. the use of social media (Variable X) on children's development (Variable Y) is moderate/enough at 0.524 or 52%, meaning that there is a positive influence on the use of social media on child development in Pulo Gebang RT.003/004 East Jakarta.